Implementasi Pembelajaran Kewirausahaan Berbasis Proyek Untuk Meningkatkan Daya Tarik dan Berpikir Kreatif Siswa di SMPN 3 Blitar - Syahrul Hikam; Nafa Amalina; Cindy Aurelia Wahyudi; Kharisma Mutiara Aisyah; Alfan Mardianto; Dewi Puspa Arum (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
This study aims to explain entrepreneurship learning and gain an understanding of the process of implementing entrepreneurship learning in increasing the attractiveness and creative thinking of students at SMP Negeri 3 Blitar. The research subfocus consists of 1). Learning models in improving the character of the entrepreneurial spirit of SMP Negeri 3 Blitar students, 2). The contribution of East Java "Veteran" UPN KKN students in improving the character of the entrepreneurial spirit of SMP Negeri 3 Blitar students, 3). The achievement of implementing entrepreneurship learning in improving the character of the entrepreneurial spirit of SMP Negeri 3 Blitar students. Research findings include: (1) improving the entrepreneurship learning model by balancing theory and practice, learning that is more focused on practical application, and realizing the objectives of the study program to produce graduates with an entrepreneurial spirit; (2) prototype design and development consists of three components: learning objectives, learning methods, and assessment; (3); and (4) learning development through the use of experimental classes.